Assisted dying – the debate: Videtur… sed contra. Issue 4 (2nd July 2014) - Graham, Philip; Hughes, Julian C.
Summary: Should the law be changed to allow health professionals to assist mentally competent, terminally ill people to end their own lives? In this article Philip Graham (P.G.) puts the arguments in favour of such a change in the law and Julian Hughes (J.H.) opposes these arguments. J.H. then sets out why he believes such a law should not be passed and P.G., in turn, sets out counterarguments. Before concluding comments, both P.G. and J.H. independently make brief closing statements supporting their own positions. LEARNING OBJECTIVES: Understand the differences between various types of 'assisted dying'. Appreciate some of the ethical arguments in favour of and against changes in the law on assisted dying in the UK. Understand some of the empirical data involved in arguments about assisted dying.